A comparative evaluation of an integrated hybrid bioreactor treating industrial wastewater - Ezechi, E.H. (Elsevier Ltd, 2019)
An integrated hybrid bioreactor (IHB) and integrated suspended bioreactor (ISB) coupling aerobic, anoxic and settling units was evaluated for industrial wastewater treatment with and without the installation of a rectangular hollow engraved submerged Perspex media in the aerobic unit. Bioreactor performance was examined at different overall hydraulic retention times of 36, 12, 7.2, 5.1 and 4 days, respectively. Nitrogen mass balance was analyzed to examine the inhibitory effects of metabolic by-products on nitrification in IHB. Both bioreactors exhibited a short start-up period during acclimatization. Results show a lower effluent COD concentration of 15â85 mg/L in IHB and 38.6â124 mg/L in ISB. Effluent ammonia-nitrogen was 0.65â3.5 mg/L in IHB and 0.3â4.5 mg/L in ISB. Effluent nitrate and nitrite were low in both bioreactors but lower in IHB. Mass balance analysis in IHB indicated that nitrate was the dominant ammonia metabolite and decreased with reducing HRT. Microfauna investigation showed that free swimmers, crawling and attached ciliates were major protozoans in IHB while free swimmers and attached ciliates were dominant protozoans in ISB. Kinetic evaluation demonstrates that microbial growth was higher in IHB. The Y, k d , Î¼ max and K s for IHB was 0.1 g VSS/g COD, 0.02 per day, 0.81 per day and 1.26 g/m 3 with a correlation coefficient (R 2 ) of 0.978 while it was 0.118 g VSS/g COD, 0.04 per day, 0.635 per day and 3.93 g/m 3 with a correlation coefficient (R 2 ) of 0.988 in ISB. This study demonstrates that while both ISB and IHB were effective for industrial wastewater treatment, IHB performance was comparatively higher due to the inclusion of the submerged media. Â© 2019 Elsevier Ltd